PRECURSOR FOR MgB2 SUPERCONDUCTING WIRE AND PRODUCING METHOD THEREOF, MgB2 SUPERCONDUCTING WIRE AND PRODUCING METHOD THEREOF, SUPERCONDUCTING MAGNET, AS WELL AS SUPERCONDUCTING DEVICE
By controlling the molar ratio and particle size of the magnesium rod and boron powder, a uniform MgB2 sintered body was formed by IMD method, which solved the problem of insufficient critical current density in MgB2 superconducting wires and achieved high-performance superconducting wires under high magnetic fields.
Patent Information
- Application Number
- JP2023123105
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
The formation of MgB2 sintered bodies in existing MgB2 superconducting wires is uneven, resulting in insufficient critical current density and cannot be effectively applied under high magnetic fields.
The magnesium diffusion method in metal tube (IMD method) is used to control the molar ratio, particle size and mixing method of magnesium rod and boron powder to ensure uniform diffusion to form a uniform MgB2 sintered body. The specific ratio and particle size range of metal tube, magnesium rod and boron powder are used, and combined with the heat treatment process, a high-density MgB2 superconducting wire is formed.
The uniform formation of MgB2 sintered body is achieved, the critical current density of superconducting wire is improved, and the performance of superconducting wire is suitable for high magnetic field environments.
Smart Images

Figure 2025019474000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a precursor for MgB2 superconducting wire and a manufacturing method thereof, an MgB2 superconducting wire and a manufacturing method thereof, a superconducting magnet, and a superconducting device. [Background technology]
[0002] MgB2 superconductor, which is one of the high-temperature superconducting materials, is a material that can be applied to superconducting magnets and electric power equipment for power saving. MgB2 superconducting wires currently on the market are formed by the powder-in-tube method (PIT method). The PIT method is a technique in which a mixed powder of magnesium and boron is packed into a metal tube, and the tube is thinned by repeatedly reducing the diameter by rolling and drawing, and then MgB2 is formed by heat treatment (see, for example, Patent Document 1 and Patent Document 2).
[0003] While the PIT method is very simple, the chemical reaction Mg+2B→MgB2 causes volume shrinkage. In addition, it is theoretically impossible to fill the powder 100%, and in practice, a superconducting wire with a porosity of about 50% is formed. As such, the MgB2 superconducting wire obtained by the PIT method contains many voids, so the magnetic field dependence of the critical current density Jc of the MgB2 superconducting wire obtained by this method is not sufficient.
[0004] To solve this problem, a method has been developed that uses magnesium rods instead of magnesium powder (see, for example, Non-Patent Document 1). This method is called the internal magnesium diffusion method (IMD) or magnesium infiltration method, and it has been reported that it achieves a nearly 100% filling rate in the obtained MgB2 region. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2002-334620 A [Patent Document 2] JP 2003-217369 A [Non-patent literature]
[0006] [Non-Patent Document 1] Shujun YE and Hiroaki Kumakura, “The development of MgB2 superconducting wires fabricated with an internal Mg diffusion (IMD) process”, IOP Publishing Ltd, Supercond. Sci. Technol. 29 (2016) 113004 (21pp) Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the IMD method, the reaction proceeds as the diffusion of magnesium progresses to the boron side, and at this time, MgB2 is formed inhomogeneously due to the difference in diffusion speed. In detail, in Non-Patent Document 1, in the heat treatment process, Mg from the magnesium rod diffuses from the center toward the sheath side, but the diffusion distance is limited. Therefore, when MgB2 is generated near the magnesium rod, the diffusion of Mg is inhibited by the generated MgB2, and Mg from the magnesium rod does not diffuse sufficiently. Therefore, MgB2 is formed inhomogeneously.
[0008] If MgB2 is formed non-uniformly, the MgB2 sintered body will be formed non-uniformly by the subsequent heat treatment, and when a magnetic field is applied to the MgB2 superconducting wire, the current will not flow in the places where the MgB2 sintered body is missing, so the area where the current can enter is limited and high critical current density characteristics cannot be obtained. For this reason, it is extremely important that the MgB2 sintered body is formed homogeneously in the MgB2 superconducting wire.
[0009] The present invention has been made to solve the above problems. That is, the object of the present invention is to provide a precursor for MgB2 superconducting wire, which is capable of obtaining MgB2 superconducting wire having a homogeneous MgB2 sintered body and capable of achieving a high critical current density, an MgB2 superconducting wire, a manufacturing method thereof, a superconducting magnet, and a superconducting device. [Means for solving the problem]
[0010] [1] A precursor for MgB2 superconducting wire comprising: a metal sheath; a magnesium rod located within the metal sheath; and a mixed powder containing at least boron powder and MgB2 powder located within the metal sheath and filled in contact with the magnesium rod, wherein the molar fraction of the MgB2 powder with respect to the total of the boron powder and the MgB2 powder is greater than 0% and less than 30%.
[0011] [2] The precursor according to the above [1], wherein when the diameter of the magnesium rod is r1 and the inner diameter of the metal sheath is r2, the relationship of 1≦r2 / r1≦4 is satisfied.
[0012] [3] The precursor according to [1] or [2] above, wherein the average particle size of the boron powder is in the range of 100 μm or less, and the average particle size of the MgB2 powder is in the range of 100 nm or more and 10 μm or less.
[0013] [4] The precursor according to [3] above, wherein the average particle size of the boron powder is in the range of 10 nm to 150 nm.
[0014] [5] The precursor according to [3] above, wherein the average particle size of the MgB2 powder is in the range of 150 nm or more and 300 nm or less.
[0015] [6] The precursor according to any one of [1] to [5] above, wherein the molar fraction of the MgB2 powder satisfies the range of 3% or more and 20% or less.
[0016] [7] The precursor according to [6] above, wherein the molar fraction of the MgB2 powder is in the range of 8% or more and 13% or less.
[0017] [8] The precursor according to any one of [1] to [7] above, wherein the mixed powder further contains carbon.
[0018] [9] The precursor according to [8] above, wherein the carbon is added to the MgB2 powder.
[0019]
[10] An MgB2 superconducting wire comprising: a linear metal sheath; and an MgB2 sintered body located within the metal sheath and having a hollow core in the longitudinal direction of the metal sheath, wherein the MgB2 sintered body contains first MgB2 crystal grains having a grain size in the range of 150 nm or more, and second MgB2 crystal grains located around the first MgB2 crystal grains and having a grain size in the range of 20 nm or more and 60 nm or less.
[0020]
[11] The superconducting wire according to
[10] above, wherein the average grain size of the first MgB2 crystal grains is in the range of 400 nm or more.
[0021]
[12] The superconducting wire according to
[10] or
[11] above, wherein the average grain size of the second MgB2 crystal grains is in the range of 35 nm or more and 55 nm or less.
[0022]
[13] A superconducting wire according to any one of
[10] to
[12] above, wherein in a cross section perpendicular to the longitudinal direction of the superconducting wire, the ratio of the cross-sectional area of the MgB2 sintered body to the cross-sectional area of the hollow core is 0.3 or more.
[0023]
[14] The superconducting wire according to any one of
[10] to
[13] above, wherein the MgB2 sintered body further contains oxygen in a range of 3 at % or more and 6 at % or less.
[0024]
[15] A method for producing a precursor for MgB2 superconducting wire, comprising: mixing boron powder and MgB2 powder so that the molar fraction of the boron powder and the MgB2 powder relative to the total of the boron powder and the MgB2 powder is greater than 0% and less than 30% to prepare a mixed powder; placing a magnesium rod in a metal sheath; and filling the mixed powder into the metal sheath in which the magnesium rod is placed.
[0025]
[16] The method according to
[15] above, wherein when the diameter of the magnesium rod is r1 and the inner diameter of the metal sheath is r2, the relationship 1≦r2 / r1≦4 is satisfied.
[0026]
[17] A method for producing an MgB2 superconducting wire, comprising: drawing the MgB2 superconducting wire precursor described in any one of [1] to [9] above; and heat treating the drawn MgB2 superconducting wire precursor in an inert gas atmosphere or in vacuum at a temperature of 550°C to 900°C.
[0027]
[18] The method according to
[17] above, wherein the heat treatment is carried out at a temperature in the range of 630°C to 750°C for a period of 1 hour to 8 hours.
[0028]
[19] A superconducting magnet comprising a superconducting coil in which the MgB2 superconducting wire according to any one of
[10] to
[14] above is wound in a coil shape.
[0029]
[20] A superconducting device comprising the superconducting magnet described in
[19] above. Effect of the Invention
[0030] According to the present invention, it is possible to provide a precursor for MgB2 superconducting wire, which is capable of obtaining MgB2 superconducting wire having a homogeneous MgB2 sintered body and capable of achieving a high critical current density, an MgB2 superconducting wire, a manufacturing method thereof, a superconducting magnet, and a superconducting device. [Brief description of the drawings]
[0031] [Figure 1]FIG. 1 is a schematic diagram of a precursor for a MgB2 superconducting wire according to an embodiment. [Diagram 2] 2A and 2B are schematic diagrams showing the steps of producing a precursor for a MgB2 superconducting wire according to an embodiment. [Diagram 3] FIG. 3 is a schematic diagram of an MgB2 superconducting wire according to an embodiment. [Figure 4] 4A and 4B are schematic diagrams showing a process of calculating the average grain size of the first crystal grains in the MgB2 superconducting wire according to the embodiment. [Diagram 5] 5A and 5B are schematic diagrams showing the manufacturing process of the MgB2 superconducting wire according to the embodiment. [Figure 6] FIG. 6 is a schematic diagram of a superconducting magnet according to an embodiment. [Figure 7] FIG. 7 is a schematic diagram of an MRI apparatus, which is an example of a superconducting device according to an embodiment. [Figure 8] FIG. 8 is an optical microscope photograph of a cross section of the MgB2 superconducting wire according to Example 1. [Figure 9] FIG. 9 is an optical microscope photograph of a cross section of the MgB2 superconducting wire according to Comparative Example 2. [Figure 10] FIG. 10 is a TEM / STEM image of the MgB2 superconducting wire according to Example 1. [Figure 11] FIG. 11 is a diagram showing STEM-EDX mapping of B, Mg, and O in a cross section of the MgB2 superconducting wire according to Example 1. [Figure 12] FIG. 12 is a diagram showing the magnetic field dependence of the critical current density of the MgB 2 superconducting wires according to Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 13] FIG. 13 is a diagram showing the magnetic field dependence of the critical current density of the MgB 2 superconducting wires according to Example 3 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, a precursor for an MgB2 superconducting wire, an MgB2 superconducting wire, methods for manufacturing them, a superconducting magnet, and a superconducting device according to embodiments of the present invention will be described. FIG. 1 is a schematic diagram of a precursor for an MgB2 superconducting wire according to this embodiment, and FIGS. 2A and 2B are schematic manufacturing process diagrams of a precursor for an MgB2 superconducting wire according to this embodiment. FIG. 3 is a schematic diagram of an MgB2 superconducting wire according to this embodiment. FIGS. 4A and 4B are schematic diagrams showing a process for calculating the average grain size of the first crystal grains in the MgB2 superconducting wire according to this embodiment. FIGS. 5A and 5B are schematic manufacturing process diagrams of an MgB2 superconducting wire according to this embodiment, FIG. 6 is a schematic diagram of a superconducting magnet according to this embodiment, and FIG. 7 is a schematic diagram of an MRI, which is an example of a superconducting device according to this embodiment.
[0033] <<<Precursor for MgB2 Superconducting Wire>>> As shown in FIG. 1, a precursor 10 for an MgB2 superconducting wire (hereinafter, may also be referred to as a "precursor") includes a metal sheath 11, a magnesium rod 12 located within the metal sheath 11, and a mixed powder 13 located within the metal sheath 11 and filled in contact with the magnesium rod 12, the mixed powder 13 containing at least boron powder and MgB2 powder.
[0034] The precursor 10 shown in FIG. 1 is cylindrical, but is not limited to being cylindrical and may be a polygonal prism. Examples of the polygonal prism include a quadrangular prism and a hexagonal prism.
[0035] The length of the precursor 10 is not particularly limited, but may be 30 mm or more. If the length of the precursor 10 is 30 mm or more, the mixed powder 13 can be filled in the metal sheath 11 without gaps. The lower limit of the above length may be 50 mm or more, or 60 mm or more. The length of the precursor 10 may be 50 mm or less.
[0036] <<Metal Sheath>> The metal sheath 11 is a cylindrical metal member. The inner diameter of the metal sheath 11 is preferably 3 mm or more and 6 mm or less. If the inner diameter of the metal sheath 11 is 3 mm or more, it is easy to fill the mixed powder 13, and if it is 6 mm or less, the thickness of the metal sheath 11 is not too thin, and damage to the metal sheath 11 can be suppressed. The lower limit of the inner diameter may be 3.2 mm or more, or 3.4 mm or more, and the upper limit of the inner diameter may be 5 mm or less, or 4.5 mm or less.
[0037] The outer diameter of the metal sheath 11 depends on the desired length of the MgB2 superconducting wire, but can be, for example, 5 mm or more and 7 mm or less. If the outer diameter of the metal sheath 11 is 5 mm or more, a long MgB2 superconducting wire can be obtained.
[0038] The material for the metal sheath 11 is not particularly limited as long as it is a material that does not easily react with magnesium and boron and is easy to process, and examples thereof include iron, CuNi alloy, titanium, niobium, and monel.
[0039] <<Magnesium rod>> The magnesium rod 12 is a rod containing magnesium and may contain impurities. The purity of magnesium in the magnesium rod 12 is preferably 80% or more. If the purity of magnesium is 80% or more, more magnesium will diffuse to the boron powder side, so more MgB2 can be produced. The lower limit of the purity is more preferably 85% or more, or 90% or more.
[0040] 1 has a cylindrical shape, the shape is not limited to a hollow cylindrical shape, and may be a polygonal prism. Examples of polygonal prisms include a square prism and a hexagonal prism.
[0041] When the diameter of the magnesium rod 12 is r1 and the inner diameter of the metal sheath 11 is r2, it is preferable to satisfy the relationship 1≦r2 / r1≦4. If r2 / r1 is 1 or more, the magnesium of the magnesium rod 12 can be sufficiently diffused in the mixed powder 13 and can be easily superconducted, and if it is 4 or less, magnesium does not become excessive, and the deterioration of workability can be suppressed and the deterioration of the critical current density can be suppressed. It is more preferable that the lower limit of the above r2 / r1 is 1.25 or more, or 1.5 or more, and the upper limit of the above r2 / r1 is 3.5 or less, or 3 or less. In addition, the quantitative relationship between the magnesium rod 12 and the mixed powder 13 is uniquely determined when the ratio between the diameter of the magnesium rod 12 and the inner diameter of the metal sheath 11 is determined, so it can be said that this ratio defines the quantitative relationship between the magnesium rod 12 and the mixed powder 13.
[0042] The diameter of the magnesium rod 12 is preferably 1 mm or more and 2 mm or less. If the diameter of the magnesium rod 12 is within this range, more MgB2 can be produced. The lower limit of the diameter of the magnesium rod 12 may be 1.2 mm or more, or 1.4 mm or more, and the upper limit may be 1.8 mm or less, or 1.6 mm or less.
[0043] <<Mixed powder>> As described above, the mixed powder 13 contains boron powder and MgB2 powder. The mixed powder 13 may further contain carbon. By further containing carbon, when the mixed powder 13 is formed into an MgB2 superconducting wire using the precursor 10 and a high magnetic field is applied to the MgB2 superconducting wire, a higher critical current density can be obtained.
[0044] <Boron powder> The molar fraction of boron powder in the total of boron powder and MgB₂ powder in the mixed powder 13 preferably satisfies the range of 70% or more and less than 100%. If the molar fraction of boron powder is 70% or more, more MgB₂ can be produced. The lower limit of the molar fraction of boron powder may be 80% or more, 85% or more, or 90% or more, and the upper limit may be 98% or less, or 96% or less. The molar ratio of boron powder and MgB₂ powder in the mixed powder 13 can be expressed by the following formula (1) when the number of moles of MgB₂ powder is x p Therefore, the molar fraction of boron powder in the total of boron powder and MgB₂ powder in the mixed powder 13 is obtained by the following formula (2), and the molar fraction of MgB₂ powder in the total of boron powder and MgB₂ powder in the mixed powder 13 is obtained by the following formula (3). B:MgB₂ = 2(1 - x p ):x p …Formula (1)
Number
Number
[0045] The average particle size of the boron powder is preferably 100 μm or less. If the average particle size of the boron powder is within this range, good reactivity with magnesium can be obtained. More preferably, the upper limit of the average particle size of the boron powder is 150 nm or less, 100 nm or less, or 50 nm or less. Also, the lower limit of the average particle size of the boron powder is not particularly limited, and for example, it may be 10 nm or more. The average particle size of the boron powder can basically be calculated by the same method as the average particle size of the second crystal grains described later. However, in calculating the average particle size of the boron powder, an SEM image is used instead of a TEM image, and after calculating each particle size from each circle described later, without selecting powders of a specific size, the average particle size is calculated by dividing the sum of each particle size by 100, which is the number of particles.
[0046] <MgB₂ powder> The molar fraction of MgB2 powder relative to the total of boron powder and MgB2 powder in the mixed powder 13 is greater than 0% and less than 30%. The lower limit of the molar fraction of MgB2 powder is more preferably 3% or more, 5% or more, or 8% or more, and the upper limit is more preferably 20% or less, 17% or less, 15% or less, or 13% or less. For example, the molar fraction of MgB2 powder is preferably in the range of 3% or more and 20% or less, more preferably 8% or more and 13% or less. The molar fraction of MgB2 powder can be measured by SEM-EDX.
[0047] The average particle size of the MgB2 powder is preferably in the range of 100 nm to 10 μm. If the average particle size of the MgB2 powder is within this range, the MgB2 powder can be dispersed homogeneously. The lower limit of the average particle size of the MgB2 powder may be 150 nm or more, or 1 μm or more, and the upper limit may be 5 μm or less, 500 nm or less, or 300 nm or less. The average particle size of the MgB2 powder can basically be calculated in the same manner as the average particle size of the first crystal grains described later. However, in calculating the average particle size of the MgB2 powder, a SEM image is used instead of a TEM image, and after calculating each particle size from each circle described later, the average particle size is calculated by dividing the sum of each particle size by 100, which is the number of particles, without selecting a powder of a specific size.
[0048] <Carbon> The carbon addition rate to the total of the boron powder and the MgB2 powder may be in the range of 0.1% or more and 30% or less, based on the total of the boron powder and the MgB2 powder in the mixed powder 13 being 100%, on a molar basis. If the carbon addition rate is 0.1% or more, the high magnetic field characteristics can be improved, and if it is 30% or less, the improvement effect of the high magnetic field characteristics can be sustained. The lower limit of the carbon addition rate may be 1% or more, or 5% or more, and the upper limit may be 20% or less, or 10% or less. The carbon addition rate can be measured by SEM-EDX. The carbon may be carbon powder. The carbon may be added to the boron powder or the MgB2 powder. When carbon is added, the ratio of each component is determined by multiplying the number of moles of the MgB2 powder by x. p Let the number of moles of carbon be xc When it is set as such, since it can be expressed by the following formula (4), the addition rate of carbon with respect to the total of boron powder and MgB2 powder is obtained by the following formula (5) on a molar basis. B:MgB2:C = 2(1 - x p ):x p :x c …Formula (4)
Number
[0049] <<<Manufacturing Method of Precursor for MgB2 Superconducting Wire>>> The precursor 10 for MgB2 superconducting wire can be obtained, for example, as follows. First, at least boron powder and MgB2 powder are mixed so that the molar fraction of MgB2 powder with respect to the total of boron powder and MgB2 powder is in the range greater than 0% and less than 30%, and a mixed powder 13 is obtained.
[0050] On the other hand, as shown in Fig. 2A, a magnesium rod 12 is disposed inside a metal sheath 11. Here, since this manufacturing method is a method for obtaining the above-mentioned precursor 10, the diameter of the magnesium rod 12 and the inner diameter of the metal sheath 11 satisfy the relationship described in the column of the above-mentioned precursor 10.
[0051] Then, as shown in Fig. 2B, the mixed powder 13 obtained above is filled into the metal sheath 11 in which the magnesium rod 12 is disposed. Thereby, the precursor 10 for MgB2 superconducting wire can be obtained.
[0052] <<<MgB2 Superconducting Wire>>> As shown in Fig. 3, the MgB2 superconducting wire 20 is obtained by using the precursor 10 for MgB2 superconducting wire. The MgB2 superconducting wire 20 includes a linear metal sheath 11 and an MgB2 sintered body 22 that is located inside the metal sheath 11 and has a hollow core 21 in the longitudinal direction of the metal sheath 11.
[0053] The uses of the MgB₂ superconducting wire 20 are not particularly limited. For example, the MgB₂ superconducting wire can be used in superconducting magnets, collective conductors, sensors, or superconducting devices equipped with any of these. A superconducting magnet using the MgB₂ superconducting wire is used, for example, in a magnetic resonance imaging device (MRI device), a nuclear magnetic resonance device (NMR device), a superconducting magnetic energy storage device (SMES device), a maglev train, an electric airplane, etc. A collective conductor is a stranded wire composed of a plurality of strands, and a collective conductor using the MgB₂ superconducting wire is used, for example, in a power transmission line, a current limiter, a transformer, a motor, etc. A sensor using the MgB₂ superconducting wire is used, for example, in a liquid hydrogen level gauge.
[0054] <<Hollow core>> The hollow core 21 is formed by diffusion of magnesium of the magnesium rod 12 into the mixed powder 13.
[0055] <<MgB₂ sintered body>> The MgB₂ sintered body 22 contains first MgB₂ crystal grains satisfying a particle size of 150 nm or more, and second MgB₂ crystal grains located around the first MgB₂ crystal grains and satisfying a particle size in the range of 20 nm or more and 60 nm or less. The first MgB₂ crystal grains are obtained from the MgB₂ powder in the mixed powder 13 of the precursor 10, and the second MgB₂ crystal grains are considered to be obtained by diffusion of magnesium of the magnesium rod 12 into boron in the mixed powder 13.
[0056] In a cross-section in a direction orthogonal to the longitudinal direction of the MgB₂ superconducting wire 20, the ratio of the cross-sectional area of the MgB₂ sintered body 22 to the cross-sectional area of the hollow core 21 (cross-sectional area of the MgB₂ sintered body 22 / cross-sectional area of the hollow core 21) is preferably 0.3 or more. If this ratio is 0.3 or more, the thickness of the MgB₂ sintered body 22 does not become too thin, so a decrease in the critical current density can be more suppressed. The lower limit of this ratio is preferably 0.35 or more, 0.375 or more, or 0.4 or more, and the upper limit is not particularly limited and may be, for example, 0.5 or less.
[0057] The MgB2 sintered body may further contain oxygen in the range of 3 at% to 6 at%. In general, oxygen produces MgO that does not exhibit superconductivity, so it is preferable to reduce the amount of oxygen as much as possible. However, it is difficult to completely prevent oxygen from being mixed into the process. In the case of the MgB2 superconducting wire according to this embodiment, even if the MgB2 sintered body contains oxygen in the range of 3 at% to 6 at%, the MgB2 superconducting wire can obtain a homogeneous MgB2 sintered body and has a high critical current density, so that strict constraints are not required during production, which is advantageous for practical use.
[0058] <First MgB2 crystal grain> The first MgB2 crystal grains satisfy the grain size of 150 nm or more. If the grain size of the first MgB2 crystal grains is 150 nm or more, a more homogeneous MgB2 sintered body 22 can be obtained. The average grain size of the first MgB2 crystal grains may be 150 nm or more, and the lower limit of the average grain size of the first MgB2 crystal grains is preferably 200 nm or more, 300 nm or more, or 400 nm or more, and the upper limit is not particularly limited, and may be, for example, 600 nm or less, or 500 nm or less. For example, the average grain size of the first MgB2 crystal grains may satisfy the range of 150 nm or more to 600 nm or less, or 400 nm or more to 500 nm or less.
[0059] The grain size and average grain size of the first MgB2 crystal grains are measured as follows. First, a TEM image is taken using a transmission electron microscope / scanning electron microscope (TEM / STEM, manufactured by JEOL Ltd., JEM-2100F). Then, the TEM image is displayed at a magnification that fits an area of 10 μm×10 μm. For 100 crystal grains observed within an area of 10 μm×10 μm and randomly selected, the crystal grains are regarded as equivalent to circles, and a circle 23 having the major axis of the crystal grain is drawn as shown in FIG. 4A.
[0060] Next, as shown in FIG. 4B, after processing the circle 23 so as to be easily measured by Image J (ver. 1.52), the area of the circle 23 is calculated, and the particle size is calculated from the calculated area. Then, all of the crystal grains having a particle size of 150 nm or more among the 100 crystal grains for which the particle size has been calculated are selected, and the average particle size is calculated by dividing the total sum of the selected particle sizes by the number of selected particles.
[0061] <Second MgB2 crystal grain> The second MgB2 crystal grains satisfy a particle size in the range of 20 nm or more and 60 nm or less. If the particle size of the second MgB2 crystal grains is 20 nm or more, the crystal grains can be maintained, and if it is 60 nm or less, a high critical current density can be obtained. The average particle size of the second MgB2 crystal grains may be 20 nm or more and 60 nm or less, and the lower limit of the average particle size of the second MgB2 crystal grains is more preferably 25 nm or more, or 30 nm or more, and the upper limit is more preferably 57 nm, or 55 nm or less. For example, the average particle size of the second MgB2 crystal grains preferably satisfies a range of 35 nm or more and 55 nm or less.
[0062] Further, since the particle size and the average particle size of the second crystal grains are smaller than those of the first crystal grains, except for using a dark field image formed from a diffraction point corresponding to the first crystal grains from an electron beam analysis pattern by TEM instead of the TEM image, it is calculated in the same manner as the first crystal grains.
[0063] <<<Method for manufacturing MgB2 superconducting wire>>> The above MgB2 superconducting wire 20 can be obtained, for example, as follows. First, as shown in FIG. 5A, the precursor 10 for the MgB2 superconducting wire is drawn. Thereby, a precursor 10 with a reduced outer diameter is obtained. The drawing process is preferably performed until the cross-sectional reduction rate of the cross-section in the direction orthogonal to the longitudinal direction of the precursor 10 becomes 90% or more. The drawing process is selected from the group consisting of, for example, grooved roll processing, flat roll processing, swaging processing, and die processing. FIG. 5A is a diagram of drawing the precursor 10 for the MgB2 superconducting wire by a swaging device 30.
[0064] Next, as shown in FIG. 5B, the drawn precursor is heat-treated in an inert gas atmosphere or in vacuum at a temperature of 550°C to 900°C. If the heat treatment temperature is within this range, Mg dissolved from the magnesium rod can react with boron to obtain an MgB2 sintered body. The lower limit of the heat treatment temperature is preferably 580°C or more, 600°C or more, or 630°C or more, and the upper limit is preferably 850°C or less, 800°C or less, or 750°C or less. Examples of inert gases include rare gases such as Ar, nitrogen, etc. In addition, the degree of vacuum when performing in vacuum is preferably 1 Pa or less.
[0065] The time of the heat treatment is preferably 1 minute or more and 50 hours or less. If the time is 1 minute or more, a MgB2 sintered body can be obtained, and if the time is 50 hours or less, an increase in cost can be suppressed. The lower limit of the time of the heat treatment is preferably 1 hour or more, and the upper limit is more preferably 8 hours or less. In particular, the heat treatment is preferably performed at a temperature range of 630°C to 750°C for 1 hour to 8 hours.
[0066] <<Superconducting magnets and superconducting devices>> As described above, the MgB2 superconducting wire 20 can be used in a superconducting magnet. As shown in Fig. 6, a superconducting magnet 40 includes a superconducting coil in which the MgB2 superconducting wire 20 is wound in a coil shape.
[0067] Such a superconducting magnet 40 can be used in a superconducting device, but here, an MRI device will be described as an example of a superconducting device. The MRI device 50 shown in Fig. 7 mainly includes a cryocontainer 51, a superconducting magnet 52 arranged in the cryocontainer 51, a gradient magnetic field coil 53 arranged inside the cryocontainer 51, an RF antenna coil (not shown) arranged inside the gradient magnetic field coil 53, and a transceiver (not shown). A measurement object is located inside the RF antenna coil. The gradient magnetic field coil 53 generates a static magnetic field having a spatial distribution at one position of the measurement object, and the RF antenna coil and the transceiver are used to apply a magnetic field of a nuclear magnetic resonance frequency to the measurement object and measure a reaction signal, thereby making it possible to perform image diagnosis of a cross section of the measurement object.
[0068] The inventors have surprisingly found that when MgB2 powder is added to the MgB2 superconducting wire precursor in addition to boron, a homogeneous MgB2 sintered body is formed in the MgB2 superconducting wire compared to when no MgB2 powder is added, and that when the MgB2 superconducting wire precursor contains an appropriate amount of MgB2 powder, a high critical current density can be obtained in the MgB2 superconducting wire. Here, the term "high critical current density" in this specification refers to a current density of 100 A / cm when a magnetic field of 10 T is applied. 2 The above critical current density is meant. According to this embodiment, in the precursor 10 for MgB2 superconducting wire, the molar fraction of MgB2 powder relative to the total of boron powder and MgB2 powder is greater than 0% and less than 30%, so that the content of MgB2 powder is appropriate. As a result, a homogeneous MgB2 sintered body 22 is formed, and an MgB2 superconducting wire 20 capable of achieving a high critical current density can be obtained. EXAMPLES
[0069] In order to explain the present invention in detail, the following examples are given, but the present invention is not limited to these descriptions. FIG. 8 is an optical microscope photograph of the cross section of the MgB2 superconducting wire according to Example 1, and FIG. 9 is an optical microscope photograph of the cross section of the MgB2 superconducting wire according to Comparative Example 2. FIG. 10 is a TEM / STEM image of the MgB2 superconducting wire according to Example 1, FIG. 11 is a diagram showing STEM-EDX mapping of B, Mg, and O in the cross section of the MgB2 superconducting wire according to Example 1, FIG. 12 is a diagram showing the magnetic field dependence of the critical current density of the MgB2 superconducting wire according to Examples 1 and 2 and Comparative Examples 1 and 2, and FIG. 13 is a diagram showing the magnetic field dependence of the critical current of the MgB2 superconducting wire according to Example 3 and Comparative Example 3. In FIG. 11, the bright areas are areas where boron (B), magnesium (Mg), or oxygen (O) exists.
[0070] In the following examples and comparative examples, the following materials were used. Metal sheath (made by Nilaco Corporation, made of pure iron): outer diameter 6 mm, inner diameter 4 mm, length 55 mm Magnesium rod (manufactured by Nilaco Corporation, purity 99.99%): diameter 2 mm, length 55 mm Boron powder (Pavezyum): average particle size 50 nm MgB2 powder: A bulk body synthesized according to the method described in JP 2018-193271 A, the particle size of which was adjusted to an average particle size of 200 nm.
[0071] The average particle size of the boron powder was calculated basically by the same method as the average particle size of the second crystal grain described below, and the average particle size of the MgB2 powder was calculated basically by the same method as the average particle size of the first crystal grain described below. However, in calculating the average particle size of the boron powder and the average particle size of the MgB2 powder, SEM images were used instead of TEM images, and after calculating each particle size from each circle described later, powder of a specific size was not selected, but the sum of each particle size was divided by 100, which is the number of particles, to obtain the average particle size.
[0072] <Example 1> First, a mixed powder of boron powder and MgB2 powder was prepared so that the molar fraction of MgB2 powder relative to the total of boron powder and MgB2 powder was 10% as shown in Table 1. The mixed powder was mixed for 24 hours using ethanol as a solvent in a ball mill. Next, a magnesium rod was placed in the center of a metal sheath as shown in Figure 1. At this time, the ratio of the inner diameter r2 of the metal sheath to the diameter r1 of the magnesium rod was 2. Next, the mixed powder was filled into the metal sheath in which the magnesium rod was placed. In this way, a precursor for MgB2 superconducting wire was obtained.
[0073] After obtaining the precursor, the precursor was wire-drawn to make the precursor wire-shaped. In detail, the diameter of the precursor was first reduced by a grooved roll rolling machine, and the precursor was finally wire-drawn to a diameter of 0.8 mm. At this time, the length of the precursor after wire-drawing was about 2 m.
[0074] Next, the drawn linear precursor was heat-treated. Specifically, the precursor was cut to a length of 35 mm, the ends were crushed by a uniaxial press, and the precursor was vacuum-sealed at a vacuum degree of 1 Pa. The precursor was then heat-treated at 690°C for 3 hours. In this way, oxidation during the heat treatment was suppressed. As a result, a MgB2 superconducting wire having a diameter of 0.8 mm and a length of 3.5 cm and including a hollow core and an MgB2 sintered body according to Example 1 was obtained. In addition, in the critical current density measurement described later, when a magnetic field of 7 T was applied to the obtained wire at 4.2 K, if a critical current was measured (see FIG. 12), it was determined that an MgB2 sintered body was produced and an MgB2 superconducting wire was obtained.
[0075] <Example 2> In Example 2, a precursor for MgB2 superconducting wire and an MgB2 superconducting wire were manufactured in the same manner as in Example 1, except that a mixed powder of boron powder and MgB2 powder was prepared so that the molar fraction of MgB2 powder relative to the total of boron powder and MgB2 powder was 5%.
[0076] <Example 3> In Example 3, a precursor for MgB2 superconducting wire and an MgB2 superconducting wire were manufactured in the same manner as in Example 1, except that a mixed powder of boron powder, MgB2 powder, and carbon powder was prepared using carbon powder such that the addition rate of carbon powder to the total of boron powder and MgB2 powder was 5% on a molar basis.
[0077] <Comparative Example 1> In Comparative Example 1, a mixed powder of boron powder and MgB2 powder was prepared so that the molar fraction of MgB2 powder relative to the total of boron powder and MgB2 powder was 30%, but the same procedures were followed as in Example 1 to produce a precursor for MgB2 superconducting wire and an MgB2 superconducting wire.
[0078] <Comparative Example 2> In Comparative Example 2, a MgB2 superconducting wire precursor and an MgB2 superconducting wire were produced in the same manner as in Example 1, except that no MgB2 powder was added, that is, the molar fraction of MgB2 was 0%.
[0079] <Comparative Example 3> In Comparative Example 3, a precursor for MgB2 superconducting wire and an MgB2 superconducting wire were manufactured in the same manner as in Comparative Example 2, except that a mixed powder of boron powder and carbon powder was prepared using carbon powder such that the addition rate of carbon powder to the total of boron powder and MgB2 powder was 5% on a molar basis.
[0080] Table 1 shows the manufacturing conditions of the MgB2 superconducting wire in Examples 1 to 3 and Comparative Examples 1 to 3. [Table 1]
[0081] <Optical microscope observation and elemental analysis> The wires according to Examples 1 to 3 and Comparative Examples 1 to 3 were cut in a direction perpendicular to the longitudinal direction of the wires, and the cross sections of the wires were observed using an optical microscope (VHX-1000, manufactured by Keyence Corporation) and a transmission electron microscope / scanning electron microscope (TEM / STEM, JEM-2100F, manufactured by JEOL Ltd.). The wire according to Example 1 was cut in a direction perpendicular to the longitudinal direction of the wires, and elemental analysis was performed on the cross sections of the wires by energy dispersive X-ray spectroscopy (EDX) attached to the TEM / STEM.
[0082] According to FIG. 8, it can be seen that in the wire according to Example 1, the MgB2 sintered body was formed in a homogeneous state near the wall surface of the metal sheath. Although not shown, in the cross sections of the samples of Example 2, Example 3, and Comparative Example 1, the MgB2 sintered body was formed throughout the metal sheath, as in Example 1. On the other hand, from FIG. 9, it can be seen that in Comparative Example 2, which used only boron powder, the MgB2 sintered body was formed only on one side of the metal sheath, and was heterogeneous. In addition, in the cross section of the sample of Comparative Example 3, the heterogeneous MgB2 sintered body was formed, as in Comparative Example 2.
[0083] In addition, the cross-sectional area of the hollow core and the cross-sectional area of the MgB2 sintered compact were measured by the above-mentioned optical microscope observation, and the ratio of the cross-sectional area of the MgB2 sintered compact to the cross-sectional area of the hollow core was calculated to be 0.41 in Examples 1 and 2 and Comparative Example 1, and 0.57 in Comparative Example 2.
[0084] 10 and 11, it can be seen that large crystal grains (first crystal grains) and small crystal grains (second crystal grains) exist in the wire of Example 1. Also, from FIG. 11, it can be seen that boron (B) exists uniformly in the wire of Example 1. Note that, according to the EDX spectrum, these crystal grains were all MgB2 crystal grains.
[0085] <Critical current density measurement> The critical current density in each magnetic field of the wires according to Examples 1 to 3 and Comparative Examples 1 to 3 was measured. Specifically, first, each wire was cut to a length of 3.5 cm, and each cut wire was heat-treated by heating it to 690°C. Then, the current-voltage (IV) characteristics of each heat-treated wire were measured by a four-terminal measurement method. The measurement was performed by changing the magnetic field using an 18T superconducting magnet (Japan Superconductor Technology Co., Ltd.) while cooling each wire by immersing it in liquid helium at 4.2K. The critical current in each magnetic field was determined from the obtained IV curve using a criterion of 1 μV / cm. Then, the obtained critical current was divided by the cross-sectional area of the wire to obtain the critical current density characteristic.
[0086] According to FIG. 12, the critical current density of the wires according to Examples 1 to 3 and Comparative Example 2 was 100 A / cm at 10 T. 2 It can be seen that the above is the case. In particular, the critical current density of the wire according to Example 1 was significantly higher than that of the wire according to Comparative Example 2. On the other hand, the critical current density of the wire according to Comparative Example 1 was 100 A / cm at 10 T. 2 It was less than.
[0087] <Measuring the average grain size> In the wire of Example 1, large crystal grains (first crystal grains) and small crystal grains (second crystal grains) were detected as described above, and the average grain size of each of the first crystal grains and the second crystal grains was measured according to the following method. The average grain size of the first crystal grains was 465 nm, and the average grain size of the second crystal grains was 54 nm.
[0088] In addition, in Comparative Example 2, as described above, large crystal grains (first crystal grains) as seen in the wire of Example 1 were not observed, but small crystal grains (second crystal grains) were observed. Therefore, the average grain size of the second crystal grains was measured according to the following method and found to be 55 nm.
[0089] The average grain size of the first crystal grains was calculated as follows. First, a TEM image taken using a transmission electron microscope / scanning electron microscope (TEM / STEM, manufactured by JEOL Ltd., JEM-2100F) was displayed at a magnification that covered an area of 10 μm×10 μm. For 100 crystal grains observed within an area of 10 μm×10 μm and randomly selected, the crystal grains were regarded as equivalent to circles, and circles having the major axis of the crystal grains were drawn.
[0090] Next, the circles were processed using Image J (ver.1.52) to make them easier to measure, and the area of each circle was calculated, and each grain size was calculated from the calculated area. Then, of the 100 grains whose grain sizes were calculated, all grains whose grain sizes were in the range of 150 nm or more were selected, and the sum of the selected grain sizes was divided by the number of selected grains to obtain the average grain size.
[0091] In addition, since the grain size of the second crystal grains is smaller than that of the first crystal grains, the grain size was calculated in the same manner as for the first crystal grains, except that a dark-field image formed from a diffraction point corresponding to the first crystal grains in a TEM electron beam analysis pattern was used instead of a TEM image.
[0092] <Oxygen measurement> The amount of oxygen in the wire according to Example 1 was measured. Specifically, the analysis was performed from STEM-EDX mapping observed at a magnification that covered an area of 10 μm×10 μm. Focusing on oxygen (O) in the EDS mapping of FIG. 11, it can be confirmed that a large amount of oxygen exists around the first crystal grains. The amount of oxygen was 4.2 at%. This value was larger than the oxygen in the wire according to Comparative Example 2. When oxygen mapping was confirmed by STEM-EDX in the wire according to Comparative Example 2, no clear oxygen mapping was observed.
[0093] Table 2 shows the results of the above measurements. [Table 2]
[0094] As described above in detail, in Comparative Example 1, a high critical current density was not obtained in the MgB2 superconducting wire, and in Comparative Examples 2 and 3, a homogeneous MgB2 sintered body was not formed in the MgB2 superconducting wire. In contrast, in Examples 1 to 3, the content of MgB2 powder in the mixed powder of the precursor for MgB2 superconducting wire was appropriate, so it was confirmed that a homogeneous and high critical current density was obtained in the MgB2 superconducting wire. Note that the critical current density of the MgB2 superconducting wire in Example 2 is lower than that of the MgB2 superconducting wire in Comparative Example 1, but when a magnetic field of 10 T was applied to the MgB2 superconducting wire, it was 100 A / cm 2 If a critical current density equal to or greater than this is obtained, it can be determined that a high critical current density has been obtained. Thus, a high critical current density was obtained in Example 2 as well. [Explanation of symbols]
[0095] 10…MgB2 superconducting wire precursor 11...Metal sheath 12…Magnesium rod 13…Mixed powder 20…MgB2 superconducting wire 21…Hollow core 22…MgB2 sintered body 40…Superconducting magnet 50...MRI device
Claims
1. A metal sheath; a magnesium rod located within the metal sheath; At least boron powder and MgB are located within the metal sheath and are filled in contact with the magnesium rod. 2 and a powder mixture containing the powder, The boron powder and the MgB 2 The MgB powder 2 The mole fraction of the powder is in the range of more than 0% and less than 30%. 2 Precursor for superconducting wire.
2. 2. The precursor according to claim 1, wherein when the diameter of the magnesium rod is r1 and the inner diameter of the metal sheath is r2, the relationship of 1≦r2 / r1≦4 is satisfied.
3. The average particle size of the boron powder is in the range of 100 μm or less, and the MgB 2 The precursor according to claim 1 , wherein the powder has an average particle size in the range of 100 nm to 10 μm.
4. The precursor according to claim 3 , wherein the average particle size of the boron powder satisfies the range of 10 nm to 150 nm.
5. The MgB 2 The precursor according to claim 3 , wherein the powder has an average particle size in the range of 150 nm to 300 nm.
6. The MgB 2 The precursor according to claim 1 , wherein the mole fraction of the powder satisfies the range of ≧3%≦20%.
7. The MgB 2 The precursor according to claim 6 , wherein the mole fraction of the powder satisfies the range of ≧8% to ≦13%.
8. The precursor of claim 1 , wherein the mixed powder further comprises carbon.
9. The carbon is the MgB 2 The precursor according to claim 8, which is added to a powder.
10. A metal sheath extending linearly; MgB2 is located within the metal sheath and has a hollow core in the longitudinal direction of the metal sheath. 2 A sintered body, The MgB 2 The sintered body is a first MgB 2 Crystal grains and the first MgB 2 A second MgB2 is located around the crystal grain and has a grain size in the range of 20 nm to 60 nm. 2 MgB 2 Superconducting wire.
11. The first MgB 2 11. The superconducting wire according to claim 10, wherein the average grain size of the crystal grains is 400 nm or more.
12. The second MgB 2 11. The superconducting wire according to claim 10, wherein the average grain size of the crystal grains is in the range of 35 nm to 55 nm.
13. In a cross section perpendicular to the longitudinal direction of the superconducting wire, the ratio of the MgB 2 11. The superconducting wire according to claim 10, wherein the ratio of the cross-sectional areas of the sintered bodies is 0.3 or more.
14. The MgB 2 11. The superconducting wire according to claim 10, wherein the sintered body further contains oxygen in a range of 3 at % or more and 6 at % or less.
15. Boron powder and MgB 2 powder, and the boron powder and the MgB 2 The MgB powder 2 mixing the powders so that the mole fraction of the powders is greater than 0% and less than 30% to prepare a mixed powder; Placing a magnesium rod within a metal sheath; Filling the mixed powder into the metal sheath in which the magnesium rod is disposed. Including MgB 2 A method for producing a precursor for superconducting wire.
16. The method according to claim 15, wherein when r1 is a diameter of the magnesium rod and r2 is an inner diameter of the metal sheath, the relationship of 1≦r2 / r1≦4 is satisfied.
17. The MgB according to claim 1 2 Drawing a precursor for a superconducting wire; The drawn MgB 2 heat-treating the precursor for superconducting wire in an inert gas atmosphere or in vacuum at a temperature of 550° C. or more and 900° C. or less; Including MgB 2 A method for manufacturing superconducting wire.
18. 18. The method of claim 17, wherein the heat treatment is carried out at a temperature in the range of 630°C to 750°C for a period of 1 hour to 8 hours.
19. The MgB according to claim 10 2 A superconducting magnet equipped with a superconducting coil made of superconducting wire wound into a coil shape.
20. 20. A superconducting device comprising the superconducting magnet of claim 19.
Citation Information
Patent Citations
Manufacturing method of mgb2 superconductive wire
JP2002334620A
Manufacturing method of magnesium diboride superconductive wire
JP2003217369A
Cited By
Superconductor, method for producing superconductor, liquid level sensor for liquid hydrogen, and liquid level gauge for liquid hydrogen
WO2026196639A1